Implementation of Control System on Automatic Shaved Ice Machine Using TFT Touchscreen Interface for Improving SME Beverage Efficiency - Agus gustiana (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The development of automation technology has significantly improved efficiency in small and medium enterprises (SMEs), particularly in beverage production processes. This study aims to design and implement an Arduino-based automatic shaved ice machine equipped with a TFT touchscreen interface to enhance efficiency, consistency, and hygiene. The research method includes mechanical and electronic system design, sensor and actuator integration, software development, and system performance testing. The system utilizes a DS18B20 temperature sensor to monitor the cooling process, an electric motor for ice shaving, and a DC pump for automatic syrup dispensing. Experimental results show that the system operates as designed, with a cooling time of approximately 30 minutes, a defrost process of 2 minutes, an ice shaving duration of 3 minutes, and syrup dispensing of 20 ml within 2 seconds. Compared to manual methods, the proposed system provides more stable, consistent, and automated operation while reducing human involvement. Therefore, the developed system effectively improves operational efficiency and product quality for SME-scale applications.